Characterization of different earthen construction materials in oasis of south-eastern Morocco (Errachidia Province). (June 2021) - Mellaikhafi, Abdellah; Tilioua, Amine; Souli, Hanène; Garoum, Mohammed; Alaoui Hamdi, Moulay Ahmed
Abstract: The oasis of Southeast Morocco possesses outstanding earthen architecture built with a mixture of rammed earth and mud brick construction. This work is a contribution to the valorization of earth building materials used in the oases to preserve this architecture against disappearance. It is a physico-chemical, mineralogical and geotechnical investigation of five soils taken from different areas on the edge of the main valleys, Wadi Ziz and Wadi Rheris, of this large oasis. First, X-ray (XRD) and infrared analyses of the soils studied show the absence of the two clay minerals, kaolinite and illite, in the oasis soils while, quartz, calcite or calcium carbonate, Ferroan Clinochlore and Muscovite are the main minerals in these soils. Second, grain size distribution, methylene blue tests and plasticity tests show that the soils of the oasis are generally low clay content and moderately plastic. They consist mainly of sand and silt. In addition, the suitability of the studied soils for the three construction techniques: adobe, rammed earth and compressed earth blocks (CEB), was tested using the recommendations cited by several authors. Furthermore, in the case of unsuitable soils, solutions are proposed to one of these techniques. The local compaction technique of rammed earth was assessed. This technique enabled us to achieve maximum dry density compaction values similar to those obtained in the laboratory using modified Proctor tests. Finally, an evaluation of the thermal conductivity of the different samples of the rammed earth walls was carried out in order to determine and compare the effect of compaction density and soil characteristics on thermal resistance. The results of this study showed that the soils taken from areas on the edge of the valley are more consistent with the construction of rammed earth. They are satisfactory in terms of compaction and also have a higher thermal resistance. Then, the construction in adobe is only possible if these soils go through a stabilization process. In addition, the grain size distribution indicated that soils taken from the soil edge are unsuitable for the manufacture of CEB.